PERSEKUTUAN KERAJAAN ACEH DARUSSALAM DENGAN TURKI UTSMANI DALAM MENGHADAPI KOLONIALISME PORTUGIS DI NUSANTARA 1537-1571 M - Muhammad Iqbal; Nuril Izzatusshobikhah; Iin Ariska Nuvitaning Sari (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2023)
The Kingdom of Aceh Darussalam was an Islamic kingdom that existed in the 16 th century. Meanwhile in the western region, the Islamic kingdom which was the last caliphate, namely the Ottoman Empire, was at the peak of its glory under the leadership of Sulaiman al-Qanuni. On the other hand, the Portuguese had succeeded in occupying Malacca and became a threat to the Islamic kingdoms in the archipelago, especially Aceh Darussalam, especially because Aceh was close to Malacca which was the main Portuguese base. The aim of this study is to determine the relationship between the Aceh Darussalam kingdom and the Ottoman Turks in fighting the Portuguese. This research includes a literature review, where in the research method stages, the author uses a historical method which has four stages, namely, heuristics, criticism, interpretation and historiography. This related research can result in the discovery that, the arrival of the Portuguese to the archipelago was motivated by trade and pressure on Muslims in the Dutch East Indies. The relationship between the Kingdom of Aceh Darussalam and the Ottoman Turks was based on several things, namely. First, the economy in which the Ottoman Turks at that time wanted to invest in the Dutch East Indies. Second, socio-political, when Aceh was colonized by the Portuguese, Aceh asked for help from the Ottoman Turks to help in the war against the Portuguese colonialists by building a military. The first visible relationship between the Aceh Darussalam kingdom and the Ottoman Turks was during the Aceh expedition against the Batak-Portuguese Alliance in 1539 M. At that time Aceh received assistance from the Turkish, Gujarat and Abbysinia Alliance with additional forces totaling 120 Turkish troops and 200 Malabar troops.